Pattern of Viruses among the Jaundiced Patients Admitted in a Tertiary Care Hospital Chattogram, Bangladesh - Rajat Sanker Roy Biswas; Sk Md Faisal Abdullah; Shemanta Waddadar; Nabil Asgor Chowdhury; Indranil Das; Mohiuddin Mohammad Alamgir (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Jaundice is the commonest presenting features of hepatitis and it is a common clinical condition in Bangladesh. As a country of the Asia Pacific region Bangladesh is considered to be a high risk country for developing hepatitis by differ ent hepatotropic viruses. This study represents the patterns and types of viruses among the patients admitted in a tertiary care hospitals in Bangladesh who were presented with jaundice. Materials and methods: Present cross sectional observational study done during a one year study period from July 2022 to June 2023 in a tertiary care hospital, Chattogram, Bangladesh among 114 patients. All patients who had clinical jaundice or having serum bilirubin > 2 mg/dl were recruited in the study. Clinical data were collected from all of them and viral serology were also done by ICT or ELISA. Informed written consent were taken from all patients and permission for the study were taken from ERB of the medical college. Results: Among 114 study subjects, male were 73(64%) and female were 41(36%) and male to female ratio was 1: 0.56. Among all, maximum were in the age range of <20 years and 21- 30 years which were 46(40.4%) and 44(38.6%) respectively. Regarding clinical features, 109(95.6%) had jaundice and 89(78.1%) had fever and 74(64.9%) had nausea and these were three dominant clinical features found. Viral serology study revealed frequency of HAV, HBV, HCV and HEV infection were 43(37.7%), 9(7.9%), 1(0.9%) and 26(22.8%) respectively. There were viral coinfections with (HAV+HEV), (HAV+HBV) and (HBV + HEV) and it were 8(7.0%), 4(3.5%) and 3(2.6%) respectively. Among all 20(17.5%) cases were tested negative for hepatotropic viruses. Again 6(5.3%) had Anti HBc Positivity and 2(1.8%) cases were found coinfected with HIV. Conclusions: In a year round, HAV and HEV are two common viral infection causing jaundice among the locality. HBV had a significant level of infection with low level HCV causing jaundice. Two HIV coinfection is an alarming condition found among the jaundice patients which need further exploration and risk factor evaluations. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 72-75